2023
DOI: 10.3390/coatings13020281
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Boosting the Perovskite Film Quality of All-Inorganic Perovskite Solar Cells

Abstract: All-inorganic CsPbX3 perovskite material not only has the benefits of advanced light absorption coefficient, long carrier lifetime, and simple preparation process of organic–inorganic perovskite materials but it also maintains excellent stability under the erosion of damp heat. Stability is the premise of its industrialization, so all-inorganic perovskite is undoubtedly a very competitive direction for the development of perovskite materials. However, there are still many defects in the all-inorganic perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…spiro-OMeTAD, for example, is among the most commonly employed HSLs in conventional-architecture devices. [68,69] However, the p-type dopants necessary to improve the charge transport capacity of the neat material contribute to poor longterm stability. Lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) absorbs ambient moisture, and 4-tert-butylpyridine (TBP) evaporates from the film, leading to the formation of voids and pinholes (Figure 3).…”
Section: Stabilitymentioning
confidence: 99%
“…spiro-OMeTAD, for example, is among the most commonly employed HSLs in conventional-architecture devices. [68,69] However, the p-type dopants necessary to improve the charge transport capacity of the neat material contribute to poor longterm stability. Lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) absorbs ambient moisture, and 4-tert-butylpyridine (TBP) evaporates from the film, leading to the formation of voids and pinholes (Figure 3).…”
Section: Stabilitymentioning
confidence: 99%
“…[22,23] Many attempts have been made to resolve this challenge, including interface engineering, strain engineering, doping, and encapsulation etc. [18,21,24] For example, DMAI and the derivative have been widely adopted as an additive for the high performance of CsPbI 3 solar cells, which slightly enhanced the stability of such devices, due possibly to the tensile strain caused by the oversized DMA þ ions in the A site. [25][26][27] However, others argue that DMAI may react with CsPbI 3 , forming double-cation hybrid perovskite Cs 1-x DMA x PbI 3 , which acted as a dopant instead of an additive.…”
Section: Introductionmentioning
confidence: 99%
“…[19] The highest reported light stability for such a device is 1000 h, far from enough for commercialization. [20,21] Worse off, the presence of water vapor in the air could accelerate the phase change, resulting in a shorter lifetime. [22,23] Many attempts have been made to resolve this challenge, including interface engineering, strain engineering, doping, and encapsulation etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective way to improve the long-term stability and thermal stability of PSCs is to completely replace the organic component of A in the ABX 3 with an inorganic component [23,24]. Since 2015, researchers have revealed that cesium lead halide PSCs have an excellent stability and the unencapsulated devices can operate continuously and stably for over 900 h at 100 • C [23,[25][26][27]. In particular, hole-transporting materials (HTM)free carbon-based cesium lead halide PSCs (C-IPSCs) exhibit two distinct advantages.…”
Section: Introductionmentioning
confidence: 99%